Question 7
To find the equation of the line in slope-intercept form that is parallel to the line \( y = 3x - 2 \) and passes through the point \( (1, -2) \), follow these steps:
-
Identify the slope of the given line: The slope-intercept form of a line is given by the equation: \[ y = mx + b \] where \( m \) is the slope. From the line \( y = 3x - 2 \), we can see that the slope \( m = 3 \).
-
Use the same slope for the parallel line: Since parallel lines have the same slope, the slope of our desired line is also \( m = 3 \).
-
Use the point-slope form of the equation: The point-slope form of a line is: \[ y - y_1 = m(x - x_1) \] Using the point \( (1, -2) \) (where \( x_1 = 1 \) and \( y_1 = -2 \)) and the slope \( m = 3 \): \[ y - (-2) = 3(x - 1) \]
-
Simplify the equation: \[ y + 2 = 3(x - 1) \] \[ y + 2 = 3x - 3 \] \[ y = 3x - 3 - 2 \] \[ y = 3x - 5 \]
Final answer: The equation of the line in slope-intercept form is \( y = 3x - 5 \).
Question 8
To find the equation of the line in slope-intercept form that is perpendicular to line \( g \) and passes through the point \( (4, 2) \), follow these steps:
-
Determine the slope of line \( g \): First, calculate the slope of line \( g \) that passes through the points \( (-3, 2) \) and \( (0, 5) \). The formula for the slope \( m \) is: \[ m = \frac{y_2 - y_1}{x_2 - x_1} \] Here \( (x_1, y_1) = (-3, 2) \) and \( (x_2, y_2) = (0, 5) \): \[ m = \frac{5 - 2}{0 - (-3)} = \frac{3}{3} = 1 \]
-
Find the slope of the perpendicular line: The slope of a line perpendicular to another is the negative reciprocal of the original slope. Thus, the slope of our desired line is: \[ m_{\text{perpendicular}} = -\frac{1}{1} = -1 \]
-
Use the point-slope form for the perpendicular line: Using the point \( (4, 2) \) and the slope \( -1 \): \[ y - 2 = -1(x - 4) \]
-
Simplify the equation: \[ y - 2 = -1(x - 4) \] \[ y - 2 = -x + 4 \] \[ y = -x + 4 + 2 \] \[ y = -x + 6 \]
Final answer: The equation of the line in slope-intercept form that is perpendicular to line \( g \) and passes through the point \( (4, 2) \) is \( y = -x + 6 \).